Positive electrode material, secondary battery and electric device

By using the positive electrode material with a core and clad structure, the structural stability is improved by using bulk-phase doped elements and high-valent doped elements, and the oxidation reaction is suppressed by the clad layer, the problem of poor structural stability of the existing positive electrode material at high voltage is solved, and the long life and efficient cycling performance of the battery are achieved.

CN119833604AActive Publication Date: 2025-04-15SOUTH CHINA UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510019052.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing positive electrode materials have poor structural stability in high voltage depth delimiting, resulting in rapid attenuation of circulation capacity, and doping-covering measures are difficult to take into account the characteristics of lithium conduction, electrical conductivity, high voltage resistance and electrolyte corrosion resistance.

Method used

The positive electrode material adopts a core and a clad structure, where the chemical formula of the core is LisNixMnyCozNnM’mO2 and the chemical formula of the clad layer is LiaNi1-bMbO2. The core contains bulk-phase doping elements and high-valent doping elements. The clad layer contains high-valent doping elements, which can improve structural stability and inhibit oxidation reactions in the deep delithiation state.

Benefits of technology

It significantly improves the thermal stability and electrochemical stability of the cathode material at high voltages, extends the service life of the battery, improves the cycle performance and high-temperature storage capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833604A_ABST
    Figure CN119833604A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material, a secondary battery and an electric device, and belongs to the technical field of batteries. The positive electrode material comprises an inner core and a coating layer arranged on the surface of the inner core, the chemical formula of the inner core is LisNixMnyCozNnM'mO2, 0.9 < = s < = 1.1, 0.33 1t, x1t, 1, 01t, y1t, 0.67, 01t, z1t, 0.67, 0 < = n1t, 0.1, 0 < = m1t, 0.05, x + y + n + m = 1, N comprises at least one of Na, Mg, Si, Ca and Sr, N comprises at least one of Na, Mg, Si, Ca and Sr, 01t, a1t, 1, 01t, b1t and 1, and the element M'and the element M are independently selected from at least one of Nb, Mo, Ru, Ta and W. The positive electrode material has high gram capacity, good structural stability and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and particularly relates to a cathode material, a secondary battery, and an electrical device. Background Art

[0002] Compared with lithium cobaltate, lithium nickelate, and lithium manganate, the cathode material (LiNi x Co y Mn 1-x-y O2) has a higher specific capacity, conductivity, and a wider working voltage. Its theoretical specific capacity is as high as 270 mAh / g, but the currently achievable actual specific capacity is only 190 mAh / g. Increasing the upper charging limit voltage of the cathode material can promote the deintercalation and intercalation of more lithium ions for reversible cycling to increase the actual specific capacity; however, it will also cause the structure to degrade easily in the deeply delithiated state, resulting in irreversible losses and rapid attenuation of the cycling capacity. Aiming at the problems of poor structural stability and cycling stability of the bulk phase and the surface and interface in the deeply delithiated state at high voltage of the cathode material, the prior art mainly solves the problems through doping - coating measures. For example, various metal oxides or oxide / carbide composite materials are coated on the surface of the cathode material to form a physical barrier to block the side reaction between it and the electrolyte, thereby improving the battery cycle life. However, it is difficult for this coating layer to simultaneously possess characteristics such as lithium conduction, conductivity, high - voltage resistance, and electrolyte corrosion resistance, often resulting in a decrease in capacity and a decline in rate performance. In addition, although doping can alleviate phase transformation to a certain extent to improve structural degradation, it cannot effectively inhibit the oxidation reaction in the near - surface region in contact with the electrolyte, and the cycling capacity still decays severely. Summary of the Invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a cathode material, a secondary battery, and an electrical device.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] In a first aspect, the present invention provides a cathode material, which includes a core and a coating layer provided on the surface of the core;

[0006] The chemical formula of the core is Li s Ni x Mn y Co z N n M’ m O2, where 0.9 ≤ s ≤ 1.1, 0.33 < x < 1, 0 < y < 0.67, 0 < z < 0.67, 0 ≤ n < 0.1, 0 ≤ m < 0.05, x + y + z + n + m = 1, and the N element includes at least one of Na, Mg, Si, Ca, Sr;

[0007] The chemical formula of the coating layer is Li a Ni 1-b M b O2, where 0 <a<1,0<b<1;

[0008] The M' element and the M element are independently selected from at least one of Nb, Mo, Ru, Ta and W.

[0009] As an embodiment of the present invention, the core satisfies: 2 μm <D v50 <10μm, D v50 It represents the particle size corresponding to 50% in the cumulative distribution of particle volume particle sizes of the inner core.

[0010] As an embodiment of the present invention, along the direction from the surface of the core to the center of the core, the mass content of the M' element within a thickness range of 200 nm accounts for more than 90% of the total mass content of the M' element.

[0011] As an embodiment of the present invention, the coating layer includes a rock salt phase containing lithium vacancies.

[0012] As an embodiment of the present invention, the coating layer at least partially and continuously wraps the surface of the core.

[0013] As an embodiment of the present invention, the coating layer satisfies: 0.5 nm<average thickness<25 nm.

[0014] As an embodiment of the present invention, the mass proportion of the coating layer in the positive electrode material is 0.1% to 1.5%.

[0015] As an embodiment of the present invention, the Li s Ni x Mn y Co z N n M' m O2 0.365≤x≤0.8, 0.05≤y≤0.3, 0.05≤z≤0.3, 0.03≤n≤0.08, 0.005≤m≤0.02; and / or, the Li a Ni 1-b M b In O2, 0.1≤a≤0.9, 0.1≤b≤0.9.

[0016] In a second aspect, the present invention provides a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises the above-mentioned positive electrode material.

[0017] In a third aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The positive electrode material of the present invention includes a core and a coating layer arranged on the surface of the core, wherein the core contains bulk doping elements and high-valent doping elements mainly distributed on the surface of the core, and the bulk doping elements can play a supporting role in the lithium layer or the metal layer, so that the positive electrode material has a higher distortion energy to improve the structural stability of the core in a deep delithiation state; and the high-valent doping elements concentrated and distributed on the surface layer of the core have a large binding energy with oxygen ions, which can inhibit the oxidation of oxygen ions and prevent the loss of lattice oxygen. In addition, the coating layer also contains high-valent doping elements, which can not only withstand high voltages and inhibit the oxidation of oxygen anions, but also reduce the surface side reactions of the positive electrode material particles and the loss of surface active substances, thereby improving the thermal stability and electrochemical stability of the positive electrode material under high voltage, thereby significantly improving the cycle performance of the battery under high voltage.

[0020] The full battery prepared by using the positive electrode material of the present invention has excellent cycle performance in the voltage range of 2.8 to 4.45V, at room temperature or at a high temperature of 45°C, and the service life of the battery is significantly extended; moreover, since the loss of surface metal ions of the positive electrode material is suppressed, the increment of the battery's cycle internal resistance is reduced; in addition, the surface and interface structural stability of the positive electrode material is enhanced, which also significantly improves the capacity retention rate of the battery stored at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of the positive electrode material of the present invention, wherein 1-core, 2-coating layer. DETAILED DESCRIPTION

[0022] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0023] According to a first aspect of the present invention, there is provided a positive electrode material, the positive electrode material comprising a core and a coating layer disposed on a surface of the core;

[0024] The chemical formula of the core is Li s Ni x Mn y Co z N n M' mO2, where 0.9 ≤ s ≤ 1.1, 0.33 < x < 1, 0 < y < 0.67, 0 < z < 0.67, 0 ≤ n < 0.1, 0 ≤ m < 0.05, x + y + z + n + m = 1, and the N element includes at least one of Na, Mg, Si, Ca, and Sr;

[0025] The chemical formula of the coating layer is Li a Ni 1-b M b O2, where 0 < a < 1, 0 < b < 1;

[0026] The M' element and the M element are independently selected from at least one of Nb, Mo, Ru, Ta, and W.

[0027] The cathode material of the present invention includes a core and a coating layer provided on the surface of the core. The core contains a bulk doping element (N element) and a high-valence doping element (M' element) mainly distributed on the surface layer of the core. The bulk doping element can play a supporting role in the lithium layer or the metal layer, so that the cathode material has a higher distortion energy to improve the structural stability of the core in the deeply delithiated state; and the high-valence doping element aggregated and distributed on the surface layer of the core has a large binding energy with oxygen ions, which can inhibit the oxidation of oxygen ions and prevent the loss of lattice oxygen. In addition, the coating layer also contains a high-valence doping element (M element), which can not only withstand high voltages, inhibit the oxidation of oxygen anions, but also reduce the surface side reactions and the loss of surface active substances of the cathode material particles, thereby improving the thermal stability and electrochemical stability of the cathode material at high voltages, and thus significantly improving the cycling performance of the battery at high voltages.

[0028] Optionally, the above Li s Ni x Mn y Co z N n M’ mThe s in O2 can be any one of 0.9, 0.95, 0.98, 1.0, 1.05, 1.1 or any two of the range values; x can be any one of 0.35, 0.4, 0.45, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or any two of the range values; y can be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65 or any two of the range values. value; z can specifically be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65 or any two of the range values; n can specifically be any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.095 or any two of the range values; m can specifically be any one of 0, 0.01, 0.02, 0.03, 0.04, 0.045 or any two of the range values.

[0029] Optionally, the above Li a Ni 1-b M b a in O2 can specifically be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, and 0.95, or any two of the range values; b can specifically be any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, and 0.95, or any two of the range values.

[0030] As an embodiment of the present invention, the core satisfies: 2 μm <D v50 <10μm, D v50 represents the particle size corresponding to 50% of the cumulative distribution of particle volume particle size of the core. v50 Specifically, the value may be any one of or any two of the ranges of 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8.5 μm, 9 μm, and 9.5 μm.

[0031] The study found that the core in the above particle size range has a suitable specific surface area, which can not only better inhibit the interface reaction to improve the high-temperature cycle performance, but also effectively shorten the lithium ion diffusion path, reduce the diffusion time, improve the rate performance, and increase the charging speed.

[0032] As an embodiment of the present invention, the mass content of M' element within a thickness range of 200 nm from the surface of the core to the center of the core accounts for more than 90% of the total mass content of M' element (ie, the total amount of M' element in the core).

[0033] The study found that when the distribution of M' elements satisfies the above relationship, it is equivalent to that most of the M' elements are concentrated in the surface layer of the inner core, thereby better inhibiting the oxidation of oxygen ions, preventing the loss of lattice oxygen, and improving electrochemical stability; the energy dispersion spectrometer in the transmission electron microscope can be used to characterize the element distribution on the material cross section to determine the mass proportion of the M' element within the 200nm thickness range of the inner core surface.

[0034] As an embodiment of the present invention, the coating layer includes a rock salt phase containing lithium vacancies.

[0035] The study found that compared with conventional layered oxides with a two-dimensional structure, the coating layer of rock salt phase oxide with a three-dimensional transition metal cation skeleton structure can not only better resist acid corrosion in electrolytes at high temperatures, but also help to better maintain the stability of the crystal structure under high delithiation state during the charging process.

[0036] As an embodiment of the present invention, the coating layer is at least partially and continuously wrapped on the surface of the core. The continuous coating layer is more conducive to forming a complete barrier layer on the surface of the core, and more effectively reducing the interface side reaction between the positive electrode material and the electrolyte.

[0037] As an embodiment of the present invention, the coating layer satisfies: 0.5nm<average thickness<25nm. Optionally, the average thickness of the coating layer can specifically be any one of 0.6nm, 1nm, 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm or any two of the range values. Studies have found that the coating layer in the above thickness range can not only form a continuous and effective coating structure, but also has little effect on lithium ion diffusion, thereby maintaining a higher capacity and better rate performance. The average thickness of the coating layer can be obtained by measuring the cross section of the positive electrode material particles by scanning electron microscopy.

[0038] As an embodiment of the present invention, the mass proportion of the coating layer in the positive electrode material is 0.1% to 1.5%. Optionally, the mass proportion of the coating layer in the positive electrode material can be any one of 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, or any two of them. Studies have found that when the mass proportion of the coating layer is 0.1% to 1.5%, the coating layer can have a suitable thickness.

[0039] As an embodiment of the present invention, the Li s Ni x Mn y Co z N n M' m O2 0.365≤x≤0.8, 0.05≤y≤0.3, 0.05≤z≤0.3, 0.03≤n≤0.08, 0.005≤m≤0.02; and / or, the Li a Ni 1-b M b In O2, 0.1≤a≤0.9, 0.1≤b≤0.9.

[0040] Optionally, the positive electrode material of the present invention can be prepared by the following preparation method:

[0041] S1. Preparation of the core: adding a lithium source, an active material precursor, and a compound containing N (bulk doping element) into a solvent in a certain proportion, then adding a complexing agent and stirring evenly, drying, and then sintering at high temperature twice to obtain a core active material;

[0042] Among them, the two high-temperature sinterings are firstly performing a high-temperature sintering, cooling down, grinding the sintered product evenly and then performing a second high-temperature sintering; the temperature of the first high-temperature sintering is 300-400°C, the time is 8-12h, and the sintering atmosphere is oxygen; the temperature of the second high-temperature sintering is 700-900°C, the time is 8-12h, and the sintering atmosphere is oxygen.

[0043] Optionally, the temperature of the first high-temperature sintering can be any one of 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C, or any two of the range values, and the time can be any one of 8h, 9h, 10h, 11h, and 12h, or any two of the range values; the temperature of the secondary high-temperature sintering can be any one of 700°C, 750°C, 800°C, 850°C, and 900°C, or any two of the range values, and the time can be any one of 8h, 9h, 10h, 11h, and 12h, or any two of the range values.

[0044] S2. Preparation of coating layer: Grind and mix the lithium source, the core active material in S1, the Ni compound and the M-containing compound in proportion, and then perform high-temperature sintering three times (temperature is 800-1000°C, time is 6-12h, sintering atmosphere is oxygen) to obtain the positive electrode material.

[0045] Optionally, the temperatures of the three high-temperature sinterings can be any one of 800°C, 850°C, 900°C, 950°C, 1000°C or any two of them, and the time can be any one of 6h, 7h, 8h, 9h, 10h, 11h, 12h or any two of them.

[0046] Wherein, the lithium source in the above steps S1 and S2 includes at least one of LiOH and Li2CO3; the N-containing compound includes at least one of N acetate, nitrate or chloride; the solvent is deionized water; the complexing agent is at least one of citric acid, malic acid and tartaric acid; the M-containing compound includes at least one of M oxide or chloride.

[0047] According to a second aspect of the present invention, there is provided a secondary battery comprising a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material described above.

[0048] According to a third aspect of the present invention, there is provided an electric device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electric device.

[0049] In order to clearly understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0050] Example 1

[0051] This embodiment provides a positive electrode material, and the preparation method thereof comprises the following steps:

[0052] S1, 9.2g of active material precursor (Ni 0.6 Mn 0.2 Co 0.2 (OH)2), 71 mg of bulk doping element salt (magnesium acetate), 100 mL of deionized water and 1.9 g of citric acid were mixed evenly (stirred and dispersed at 400 rpm for 4 h), and then vacuum dried to obtain a mixed raw material;

[0053] S2, mixing the mixed raw material in S1 with 2.4 g of lithium hydroxide, grinding them evenly, and calcining them at 400° C. for 10 h in an oxygen atmosphere to obtain a sintered product; then grinding the sintered product evenly, and calcining it at 800° C. for 10 h in an oxygen atmosphere to obtain a magnesium-doped active material;

[0054] S3, firstly mix lithium carbonate, tantalum pentoxide and nickel oxide in a molar ratio of 1:4:2.1 (wherein lithium carbonate is 1.85 mg), then mix them evenly with the magnesium-doped active material in S2, and calcine them at 900°C for 8h in an oxygen atmosphere to obtain a positive electrode material (schematic diagram as shown in FIG. Figure 1 shown).

[0055] Embodiment 2-3

[0056] Embodiments 2 and 3 provide a positive electrode material. The positive electrode material is different from that of embodiment 1 in that the core Li s Ni x Mn y Co z N n M' m The atomic ratios of Ni, Mn, Co, and N (bulk doping elements) in O2 are different.

[0057] Embodiment 4-5

[0058] Embodiments 4 and 5 provide a positive electrode material. The positive electrode material is different from that of embodiment 1 in that the core Li s Ni x Mn y Co z N n M' m The types of N elements (bulk doping elements) in O2 are different.

[0059] Embodiment 6-7

[0060] Embodiments 6 and 7 provide a positive electrode material. The positive electrode material is different from that of embodiment 1 in that the core Li s Ni x Mn y Co z N n M' m The particle size of O2 is different.

[0061] Embodiments 8 to 9

[0062] Embodiments 8 to 9 provide a positive electrode material. The positive electrode material is different from that of embodiment 1 in that the coating layer Li a Ni 1-b M b The atomic ratios of Li, Ni and M elements in O2 are different.

[0063] Embodiments 10 to 11

[0064] Embodiments 10 to 11 provide a positive electrode material. The positive electrode material is different from that of embodiment 1 in that the core Li s Ni x Mn y Co z N n M' m M' elements in O2 and Li coating a Ni 1-b M b The types of M elements in O2 are different.

[0065] Embodiments 12 to 13

[0066] Embodiments 12 to 13 provide a positive electrode material, which is different from that of embodiment 1 in that the average thickness and mass content of the coating layer in the positive electrode material are different.

[0067] Embodiment 14

[0068] Embodiment 14 provides a positive electrode material, which is different from that of embodiment 1 in that the core Li s Ni x Mn y Co z N n M' m The doping amount of N element (bulk doping element) in O2 is 0.

[0069] Embodiments 15-16

[0070] Embodiments 15 to 16 provide a positive electrode material, which is different from Embodiment 1 in that the temperature and time of calcination in step S3 are adjusted so that the mass proportion of the M' element within the 200nm thickness range from the surface to the center of the core is different.

[0071] Comparative Example 1

[0072] Comparative Example 1 provides a positive electrode material, which is different from Example 1 in that the core Li s Ni x Mn y Co z N n M' m N, M' elements in O2 and Li coating layer a Ni 1-b M b The doping amount of the M element in O2 is 0.

[0073] Comparative Example 2

[0074] Comparative Example 2 provides a positive electrode material, which is different from Example 1 in that the positive electrode material has no coating layer and the core Li s Ni x Mn y Co z N n M' m The doping amount of N and M' elements in O2 is 0.

[0075] Table 1 Positive electrode materials in various embodiments and comparative examples

[0076]

[0077] Table 1 Li s Ni x Mn y Co z N n M' m s=1 in O2;

[0078] D v50 is the particle size corresponding to 50% in the cumulative distribution of particle volume particle size of the core in the positive electrode material, μm;

[0079] c is the mass content of the coating layer in the positive electrode material, %;

[0080] d is the average thickness of the coating layer in the positive electrode material, nm;

[0081] e is the ratio of the mass content of the M' element within a thickness range of 200 nm from the surface of the core to the center of the core in the core of the positive electrode material to the total mass content of the M' element.

[0082] The particle size D of the core in the above positive electrode material V50 It can be measured by a laser particle size analyzer; the average thickness of the coating layer can be obtained by measuring the cross section of the positive electrode material particles using a scanning electron microscope.

[0083] The ratio of the mass content of the M' element within a thickness range of 200 nm from the surface of the core to the center of the core in the above-mentioned positive electrode material to the total mass content of the M' element can be determined by characterizing the element distribution on the material cross section using an energy dispersion spectrometer in a transmission electron microscope.

[0084] Performance Testing

[0085] A positive electrode sheet is made by taking the positive electrode material in each embodiment and comparative example as the positive electrode active material, and then the positive electrode sheet, the negative electrode sheet and the diaphragm sheet are stacked in order so that the diaphragm is located between the positive and negative electrode sheets, and a bare battery cell is obtained by winding, hot pressing and shaping, and welding the tabs; then the bare battery cell is placed in an outer packaging aluminum-plastic film, and baked in an oven at 85±10°C for 24h, and the electrolyte is injected into the dried battery, and a lithium-ion soft-pack battery is obtained by standing, forming, and dividing the capacity.

[0086] 1) The positive electrode sheet is prepared by the following preparation method: the positive electrode material prepared in each embodiment and comparative example, the conductive agent acetylene black, the dispersant PVP and the binder polyvinylidene fluoride are dispersed in NMP according to a mass ratio of 97.3:0.6:0.2:1.9 to prepare a slurry, which is then coated on both sides of an aluminum foil, and the positive electrode sheet (surface density of 0.22 g / 1540.25 mm2) is obtained after baking, rolling and cutting. 2 ).

[0087] 2) The negative electrode sheet is prepared by the following preparation method: artificial graphite, conductive agent acetylene black, thickener CMC and binder SBR are mixed and dispersed in deionized water in a mass ratio of 96.4:0.8:1.5:1.3 to prepare a slurry, which is then coated on both sides of the copper foil, and then baked, rolled and cut to obtain a negative electrode sheet (surface density of 0.135g / 1540.25mm 2 ).

[0088] 3) Preparation of electrolyte: EC and DMC were mixed evenly in a volume ratio of 1:1, and then lithium hexafluorophosphate was added in a glove box to prepare an electrolyte with a concentration of 1 mol / L.

[0089] The above soft-pack battery was subjected to charge and discharge tests. The specific test method is as follows and the test results are shown in Table 2.

[0090] Test method:

[0091] 1) Room temperature discharge specific capacity test: At 25±2° C., the soft-pack batteries obtained in each embodiment and comparative example were subjected to constant current charge and discharge tests at a rate of 0.33C in a working range of 2.8 to 4.4V.

[0092] 2) Normal temperature cycle performance test: At 25±2°C, the soft-pack batteries obtained in each embodiment and comparative example were subjected to 500 charge and discharge cycle tests in the range of 2.8 to 4.4V at a charge and discharge rate of 0.33C, and the discharge capacity retention rate was recorded; 500-cycle capacity retention rate (%) = discharge specific capacity of the 500th cycle / discharge specific capacity of the 1st cycle × 100%.

[0093] 3) High temperature cycle performance test: At 45±2°C, the soft-pack batteries obtained in each embodiment and comparative example were subjected to 500 charge and discharge cycle tests in the range of 2.8 to 4.4V at a charge and discharge rate of 0.33C, and the discharge capacity retention rate was recorded; 500-cycle capacity retention rate (%) = 500th cycle discharge specific capacity / 1st cycle discharge specific capacity × 100%.

[0094] 4) Internal resistance test: The soft-pack batteries obtained in each embodiment and comparative example were subjected to a high temperature cycle test, taken out after 500 cycles, the SOC was adjusted to 50%, and discharged at a rate of 1C for 10s. The voltage difference before and after discharge was recorded, and the resistance value was obtained using Ohm's law.

[0095] Table 2 Performance of soft-pack batteries corresponding to various embodiments and comparative examples

[0096]

[0097] According to the data in Table 2, the discharge specific capacity of Examples 1 to 16 is ≥170 mAh / g, the 500-cycle capacity retention rate at 25°C is ≥85%, and the 500-cycle capacity retention rate at 45°C is ≥75%, and the DCR internal resistance after 500 cycles at high temperature (45°C) is ≤116 mΩ, indicating that the positive electrode material of the present invention has high gram capacity, good structural stability and excellent cycle performance.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A positive electrode material, characterized in that: It comprises a core and a coating layer arranged on the surface of the core; The chemical formula of the core is Li s Ni x Mn y Co z N n M’ m O2, where 0.9 ≤ s ≤ 1.1, 0.33 < x < 1, 0 < y < 0.67, 0 < z < 0.67, 0 ≤ n < 0.1, 0 ≤ m < 0.05, x + y + z + n + m = 1, and the N element includes at least one of Na, Mg, Si, Ca, and Sr; The chemical formula of the coating layer is Li a Ni 1-b M b O2, where 0 <a<1,0<b<1; The M' element and the M element are independently selected from at least one of Nb, Mo, Ru, Ta and W.

2. The positive electrode material according to claim 1, characterized in that The core meets: 2μm <D v50 <10μm, D v50 It represents the particle size corresponding to 50% in the cumulative distribution of particle volume particle sizes of the inner core.

3. The positive electrode material according to claim 1, characterized in that Along the direction from the surface of the core to the center of the core, the mass content of the M' element within a thickness range of 200 nm accounts for more than 90% of the total mass content of the M' element.

4. The positive electrode material according to claim 1, characterized in that The coating layer includes a rock salt phase containing lithium vacancies.

5. The positive electrode material according to claim 1, characterized in that The coating layer at least partially and continuously wraps the surface of the core.

6. The positive electrode material according to claim 1, characterized in that The coating layer satisfies: 0.5nm<average thickness<25nm.

7. The positive electrode material according to claim 1, characterized in that The mass proportion of the coating layer in the positive electrode material is 0.1% to 1.5%.

8. The positive electrode material according to claim 1, characterized in that The Li s Ni x Mn y Co z N n M' m In O2, 0.365≤x≤0.8, 0.05≤y≤0.3, 0.05≤z≤0.3, 0.03≤n≤0.08, 0.005≤m≤0.02; and / or, the Li a Ni 1-b M b In O2, 0.1≤a≤0.9, 0.1≤b≤0.

9.

9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Lithium-doped modified high-nickel low-cobalt ternary positive electrode material for lithium ion battery, and preparation method thereof

    CN112768687A

  • Coating material for coating positive electrode active material, positive electrode composite material, preparation method of positive electrode composite material, positive plate and battery

    CN113921816A

  • Positive electrode material and application thereof

    CN114430037A

  • Lithium battery positive electrode material as well as preparation method and application thereof

    CN116868367A

  • Lithium-rich manganese-based positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric equipment

    CN117712343A